Estimating the Amount of Information Conveyed by a Population of Neurons - Crumiller, Marshall; Knight, Bruce; Yu, Yunguo; Kaplan, Ehud (Frontiers in Neuroscience, 2011)
Recent technological advances have made the simultaneous recording of the activity of many neurons common. However, estimating the amount of information conveyed by the discharge of a neural population remains a significant challenge. Here we describe our recently published analysis method that assists in such estimates. We describe the key concepts and assumptions on which the method is based, illustrate its use with both simulated neurons and real data recorded from the lateral geniculate nucleus (LGN) of a monkey, and show how it can be used to calculate redundancy and synergy among neuronal groups.